2017
DOI: 10.15171/ehem.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Removal of acid red 88 from wastewater by adsorption on agrobased waste material. A case study of Iranian golden Sesamum indicum hull

Abstract: Background: Colors are very useful in different industries such as textile and leather but when they enter water, can cause many biological and environmental problems. In the present research, a waste agricultural material which is freely available is employed to analyze its efficiency for removing acid dye from contaminated wastewaters. Methods: In this study, batch adsorption experiments were performed in the treatment process of acid red 88 (AR88) by Iranian golden Sesamum indicum (IGSI) seeds hull which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…According to the assumption of the Langmuir isotherm model, the adsorption of DB129 onto modified zeolite occurred as a monolayer on the surface. A similar observation was reported for the adsorption of acid red 88 on Iranian golden Sesamum indicum hull (19), Congo red on rice husk (42) and methylene blue on pineapple stem waste (43).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…According to the assumption of the Langmuir isotherm model, the adsorption of DB129 onto modified zeolite occurred as a monolayer on the surface. A similar observation was reported for the adsorption of acid red 88 on Iranian golden Sesamum indicum hull (19), Congo red on rice husk (42) and methylene blue on pineapple stem waste (43).…”
Section: Discussionsupporting
confidence: 85%
“…After mixing, zeolites were washed with distilled water, passed through the appropriate filter and dried at 105°C for 12 hours (18). The experiments were performed according to Zarei et al (19). 400 mL graduated cylinder containing 100 mL dye solution was utilized, in which the adsorbent was added.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation coefficients of five isotherm models under study (Figure 7) shows that the Langmuir isotherm, with a correlation coefficient of 0.9864 is the most suitable model for the adsorption of AO7 using RB/PANI adsorbent. Since the Langmuir isotherm is only valid for the adsorption of adsorbate in aqueous solutions by bioadsorbents with limited number of unified sites in a single layer, it can be concluded that AO7 dye is adsorbed by RB/ PANI in a single layer and relatively monotonous state (40). Based on the results of Table 3, there is a significant difference between the equilibrium adsorption capacity (q e (exp) ) and calculated equilibrium adsorption capacity (q e (cal) ) for pseudo-first-order model.…”
Section: Discussionmentioning
confidence: 99%